2001
DOI: 10.1074/jbc.m107892200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protein Kinase C in the Signal Pathways That Link Na+/K+-ATPase to ERK1/2

Abstract: We have shown before that Na ؉ /K ؉ -ATPase acts as a signal transducer, through protein-protein interactions, in addition to being an ion pump. Interaction of ouabain with the enzyme of the intact cells causes activation of Src, transactivation of EGFR, and activation of the Ras/ ERK1/2 cascade. To determine the role of protein kinase C (PKC) in this pathway, neonatal rat cardiac myocytes were exposed to ouabain and assayed for translocation/ activation of PKC from cytosolic to particulate fractions. Ouabain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 51 publications
2
99
1
Order By: Relevance
“…Functionally, the activated PLC-␥1 was able to convert PIP2 to IP3 and DAG and inhibition of PLC abolished ouabaininduced calcium transients in LLC-PK1 cells ( Figure 10C). This is consistent with our recent observation that ouabainactivated Na/K-ATPase stimulated PKCs in cardiac myocytes (Mohammadi et al, 2001). In addition, we found that ouabain stimulated tyrosine phosphorylation of IP3R2 (Figures 7 and 8).…”
Section: Regulation Of Plc-␥1 and Ip3r2 By The Activated Na/katpase Ssupporting
confidence: 82%
“…Functionally, the activated PLC-␥1 was able to convert PIP2 to IP3 and DAG and inhibition of PLC abolished ouabaininduced calcium transients in LLC-PK1 cells ( Figure 10C). This is consistent with our recent observation that ouabainactivated Na/K-ATPase stimulated PKCs in cardiac myocytes (Mohammadi et al, 2001). In addition, we found that ouabain stimulated tyrosine phosphorylation of IP3R2 (Figures 7 and 8).…”
Section: Regulation Of Plc-␥1 and Ip3r2 By The Activated Na/katpase Ssupporting
confidence: 82%
“…In addition, these new findings support the hypothesis that the Na/KATPase is an important receptor capable of transmitting ouabain signals via protein kinases (4,5,9,33,34). Finally because Src is actively involved in control of cell growth (35), our new findings warrant the need for re-examining the issue of whether the Na/KATPase-mediated repression of Src and ouabain-provoked activation of Src play a role in cancer biology.…”
Section: Discussionsupporting
confidence: 59%
“…Additionlly, interaction of ouabain with cardiomyocyte Na + /K + ATPase triggers EGFR transactivation and Ras/ERK1/2 activation (Haas et al, 2000), with PKC essential to this signalling (Mohammadi et al, 2001), though whether up-and/or downstream of EGFR is untested.…”
Section: Pkcmentioning
confidence: 99%